$q_e-$Fixed Point and $q_e-$Inverse Function Theorem $1D$ - Castillo, J. A.; Moyado, J. A. P.; Galeana, T.; Herrera, M.A.; Herrera, Israel (Discontinuity, Nonlinearity, and Complexity, 2026)
Using the definitions from [1] on the $q_e-$calculus we prove $q_e-$analogues of the Fixed Point Theorem and Inverse Function Theorem.